La lingua c’è. Saussure, Chomsky e Lacan - Cimatti, Felice (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
Ferdinand de Saussure discovered that language does exist by itself. Language is not a means of communication, quite the contrary; communication can exist because previously there is language. In this paper, the subordinate position of the speaker is analyzed in respect to the autonomous language device. The possibility of a way out from such a condition is examined, using the Lacanian theorization about the concept of the “real”.